A novel type solar assisted heat pump using a low GWP refrigerant (R-1233zd(E)) with the flexible solar collector. (15th April 2018) - Lee, Seung Joo; Shon, Byung Hoon; Jung, Chung Woo; Kang, Yong Tae
Abstract: Low GWP refrigerants have been extensively paid attention to solve the environmental problems. Meanwhile, the integration of systems such as a solar assisted heat pump has been also developed consistently to compensate shortcomings of individual systems and enhance the efficiency of the system. In this study, the performance of the novel type solar assisted heat pump system using a low GWP refrigerant (R-1233zd(E)) with the flexible solar collector is investigated by experiments. R-1233zd(E) is a low GWP refrigerant with GWP lower than 7.0. The performance of solar assisted heat pump system using R-1233zd(E) is firstly compared with that using R-134a. From the study, it is found that the flexible solar collector shows the average efficiency of 40% irrespective of the weather conditions. In addition, high performance of the solar assisted heat pump using R-1233zd(E) is obtained by controlling the mass flow rate and heat source temperature. Finally, although the heat capacity of the solar assisted heat pump using R-1233zd(E) is lower than that with R-134a at same conditions, COP of the system using R-1233zd(E) shows a higher value due to low power consumption rate compared to that using R-134a. Highlights: A novel type of flexible solar collector is developed. Performance of SAHP using R-1233zd(E) is firstly compared with that using R134a. The flexible solar collector shows the average efficiency of 40% irrespective of the weather conditions. COP of heat pump using R-1233zd(E) shows a higher value than that using R-134a.